Ware potato harvesting and storage techniques: guidelines for harvesting and storage management of ware potato. - Wasukira, A.; Walimbwa, K.; Wobibi, S.; Owere, L.; Naziri, D.; Parker, M. (2017)
Potatoes are commonly regarded as a bulky, perishable commodity with high transport costs and limited export potential, confined mostly to cross-border transactions. The potato is a good source of dietary energy and some micronutrients, and its protein content is very high in comparison with other roots and tubers. Fresh potato consumption is the major form of utilization, however processing has improved to meet rising demand from the fast food, snack and convenience food industries. The growing urban populations, rising incomes, the diversification of diets and lifestyles is the driver behind this new development. This guide therefore gives the basic principles for potato harvesting and storage to ensure good quality ware potato for enhanced market access and better prices.